Identifikasi Pola Aliran Air Tanah di Lapangan Panas Bumi Non-Vulkanik Desa Nyelanding Kabupaten Bangka Selatan Berdasarkan Anomali Self-Potential - Widyaningrum, Yekti; Indriawati, Anisa; Afni, Githa Nurvilia; Gusnia, Eri; Kusmita, Tri (Jurusan Fisika, Universitas Bangka Belitung, 2023)
As one of unique non-volcanic geothermal field in Indonesia, mapping the groundwater flow in Nyelanding Village, South Bangka is essential as preliminary study for further exploration activity if the geothermal manifestation. In order to achieve this goal, we conduct a research using natural electrical properties of subsurface, Self-Potentials (SP) method. In this study, fixed-based technique was used where the spacing between measurement stations is the multiplication of 10 m along three lines at the study area. Raw field data (potential value) was corrected to diurnal and closure corrections. Further, SP anomaly was plotted and combined with topography data to be analyzed. The result shows potential value raging from -25mV to 100mV which in agreement with the lowest and highest elevation in topography map, respectively. This means, these values are controlled by topographic feature in the study area. Thus, in conclusion, the groundwater flows from the West to North East and South East part of the study area